Socio-demographic perspectives on the COVID-19 pandemic - Swanson, David A. 1946-; Verdugo, Richard R. (Emerald Publishing Limited : Information Age Publishing, Inc., 2024)
"The present volume undertakes socio-demographic analyses of four major topics surrounding the Covid-19 pandemic: Data Issues; Statistical Modeling; Analyses; and Policy Concerns. Regarding Data Issues, three chapters cover topics about obtaining reliable information; the production of summary statistics and using the geometric mean; and the importance of using a Demographic framework in better understanding the Covid-19 pandemic. Statistical modeling is a second topic, and is covered by three chapters. To begin with, one approach centers on modeling local areas. A second chapter discusses and provides a simple method for estimating the number of unconfirmed Covid-19 cases in a local area; a third chapter undertakes an examination of early warnings and responses. Analysis is a third topic and is covered by four chapters. The first chapter under this topic covers the effects of race and age on Covid-19. A second chapter examines the effects of Covid-19 on the broadband access and Census 2020 results for the Hopi and Lummi reservations. A third chapter examines the Black Lives Matters activism during the Covid-19 pandemic. A final chapter in this section examines the relative risk of dying from Covid-19 among those infected. A final topic focuses on policy issues. The first chapter under this topic examines partisan politics and Covid-19. A second chapter examines US policy and Covid-19 cases and deaths. A third chapter examines Covid-19 mortality rates and race-ethnic differences. A fourth chapter examines anti-Asian hate during the Covid-19 pandemic. A final chapter looks at America's post-pandemic future"--